G Protein-Coupled Receptors (GPCRs) in Alzheimer’s Disease: A Focus on BACE1 Related GPCRs - Zhao, Juan; Deng, Yulin; Jiang, Zhaotan; Qing, Hong (Frontiers in Aging Neuroscience, 2016)
The G protein coupled receptors (GPCRs) have been considered as one of the largest families of validated drug targets, which involve in almost overall physiological functions and pathological processes. Meanwhile, Alzheimer’s disease (AD), the most common type of dementia, affects thinking, learning, memory and behavior of elderly people, that has become the hotspot nowadays for its increasing risks and incurability. The above fields have been intensively studied, and the link between the two has been demonstrated, whereas the way how GPCRs perturb AD progress are yet to be further explored given their complexities. In this review, we summarized recent progress regarding the GPCRs interacted with β-site APP cleaving enzyme 1 (BACE1), a key secretase in AD pathogenesis. Then we discussed the current findings on the regulatory roles of GPCRs on BACE1, and the possibility for pharmaceutical treatment of AD patients by the allosteric modulators and biased ligands of GPCRs. We hope this review can provide new insights into the understanding of mechanistic link between GPCRs and BACE1, and highlight the potential of GPCRs as therapeutic target for AD.